أثر استخدام بعض الأغاني العربية كموروث ثقافي لدى تلاميذ المرحلة الإعدادية - الضويني، دعاء منير محمود; تفاحة، جمال السيد; صقر، عطيات محمد; زيتون، منى مصطفى السيد (جامعة بورسعيد - كلية التربية النوعية, 2020)
يهدف البحث الحالي إلى تقديم بعض الأغاني العربية المقترحة كموروث للثقافة الموسيقية لدى تلاميذ المرحلة الإعدادية باستخدام اختبار تحصيلي موسيقي من أعداد الباحثة. وأيضا الكشف عن أثر استخدام بعض الأغاني العربية المقترحة لتنمية الجانب المعرفي والجانب المهارى كموروث ثقافي الموسيقي. وقد تكونت عينة البحث من (40) طالبة من طالبات الصف الثاني الإعدادي بمدرسة الزهور الإعدادية بنات بمدينة بورسعيد مقسمة إلى مجموعتين المجموعة الضابطة وعددها (٢٠) طالبات تدرس بالطريقة المتبعة، والأخرى تجريبية وعددها (20) وتدرس باستخدام بعض الأغاني العربية كموروث ثقافي. واعتمد البحث على المنهج الوصفي التحليلي، يسعى البحث إلى التأكد من مدى صحة بأنه لا توجد فروق ذات دلالة إحصائية عند مستوى ≥ (0.05) بين متوسطي درجات طلاب المجموعة الضابطة (مستخدم معها الطريقة التقليدية في التدريس) والمجموعة التجريبية (المستخدم معها بعض الأغاني العربية كموروث ثقافي) وذلك في التطبيق القبلى للاختبار التحصيلي للثقافة الموسيقية، ووجود فروق ذات دلالة إحصائية عند مستوى ≥ (0.05) بين متوسطي درجات طلاب المجموعة الضابطة (المستخدم معها الطريقة التقليدية في التدريس) والمجموعة التجريبية (المستخدم معها بعض الأغاني العربية كموروث ثقافي) وذلك في التطبيق البعدي للاختبار التحصيلي للثقافة الموسيقية، وتوصل البحث إلى فاعلية أثر استخدام بعض الأغاني العربية كموروث ثقافي لدى تلاميذ المرحلة الإعدادية. The current research aims to present some suggested Arabic songs as a legacy of the musical culture of middle school students using a musical achievement test prepared by the researcher. And also revealing the effect of using some of the proposed Arabic songs to develop the cognitive side and the skill side as a cultural heritage of music. The research sample consisted of (40) female students from the second preparatory year at Al -Zohour Preparatory School for Girls in Port Said, divided into two groups: the control group, the number of (20) students studying in the usual way, and the other experimental group, numbering (20), studying using some Arabic songs as a cultural heritage. The research relied on the analytical descriptive approach. The research seeks to ascertain the validity of the fact that there are no statistically significant differences at the level <(0.05) between the mean scores of the students of the control group (using the traditional method of teaching) and the experimental group (using some Arabic songs as a legacy). Cultural) in the pre-application of the achievement test of musical culture, and there are statistically significant differences at the level <(0.05) between the mean scores of the students of the control group (the traditional method of teaching is used) and the experimental group (some Arabic songs are used as a cultural heritage) in the application The post-test of the achievement of musical culture, and the research found the effectiveness of the effect of using some Arabic songs as a cultural heritage among middle school students.
Keywords: التراث الشعبي -- الأغاني العربية -- الثقافة الموسيقية -- طلبة المدارس -- التعليم الإعدادي